Coordinated economic dispatch of AC/DC hybrid microgrids considering energy storage degradation - Cui, Boyuan (Nanyang Technological University, 2022)
AC/DC hybrid microgrids have gained more attention due to the increase of DC power source and loads. Therefore, the coordinated dispatch is necessary for economical and reliable operations of AC/DC hybrid microgrids.